2014
DOI: 10.1002/eji.201343907
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 influences the migration of B cells during maturation

Abstract: The atypical chemokine receptor CXCR7 binds the chemokines CXCL12 and CXCL11. The receptor is widely expressed and was shown to tune CXCR12-induced responses of CXCR4. Here, the function of CXCR7 was examined at late stages of human B-cell maturation, when B cells differentiate into Ab-secreting plasmablasts. We identified two populations of CXCR7 + cells in tonsillar lymphocytes, one being presumably memory potential contribution of the scavenger receptor in final B-cell maturation. On in vitro differentiatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 62 publications
0
32
1
Order By: Relevance
“…Notwithstanding this possibility, the notion of a specific role for MIF/CXCR7 was further substantiated by the observation that MIF‐mediated B‐cell chemotaxis was similarly inhibited by the CXCR4 antagonist AMD3100, confirming prior results (14), whereas CXCL12‐mediated B‐cell chemotaxis was blocked by AMD3100 but not by anti‐CXCR7 antibody. The latter result was in contrast to prior data showing that antibody‐based CXCR7 blockade led to an increase in migration (29, 45). This discrepancy could be caused by the cell type used (primary murine splenic B cells) or antibody dose applied.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding this possibility, the notion of a specific role for MIF/CXCR7 was further substantiated by the observation that MIF‐mediated B‐cell chemotaxis was similarly inhibited by the CXCR4 antagonist AMD3100, confirming prior results (14), whereas CXCL12‐mediated B‐cell chemotaxis was blocked by AMD3100 but not by anti‐CXCR7 antibody. The latter result was in contrast to prior data showing that antibody‐based CXCR7 blockade led to an increase in migration (29, 45). This discrepancy could be caused by the cell type used (primary murine splenic B cells) or antibody dose applied.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, one study showed that CXCL12 signals through CXCR7 to promote T‐cell migration, an effect that was reduced by a CXCR7‐blocking antibody (19), whereas in another study, blockade of CXCR7 with a neutralizing antibody or the small‐molecule compound CCX733 showed no impact on CXCL12‐enhanced T‐cell chemotaxis (61). In B lymphocytes, Humpert et al (45) demonstrated that blocking CXCR7 in in vitro ‐differentiated cells enhances CXCR4‐dependent migration of B cells toward CXCL12, implicating CXCR7 in the migration of B cells during maturation. We found that targeting CXCR7 with a neutralizing antibody significantly inhibited splenic B‐cell chemotaxis in response to MIF, whereas CXCL12‐mediated chemotaxis of primary B cells was not affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the scavenging activity of the receptor is essential to prevent CXCR4 down-regulation, e.g., during migration of interneurons [44,45]. Recently, it was shown that ACKR3 expression on CXCR4 + plasma blasts licenses them to leave CXCL12-rich germinal centers [46]. Under inflammatory conditions when endothelial cells up-regulate ACKR3, the receptor promotes infiltration of leukocytes into the brain parenchyma through scavenging of perivascular CXCL12 at the basal site of brain blood microvessels [47].…”
Section: Ligand-biased Signaling and Its Role In Chemokine Biologymentioning
confidence: 99%
“…Previous research has shown that human breast adipose-derived stem cells (HBASCs) transfected with CXCR4 can enhance the survival and quality of transplanted free fat tissues in nude mice [26]. CXCR7, an atypical chemokine receptor that binds CXCL12 and CXCL11 [27], has also been shown to associate with CXCR4 and regulate CXCR4/SDF-1-mediated processes, such as the migration of plasmablasts during B-cell maturation [28]. However, the CXCR7-mediated cellular responses to CXCL12 are still largely unknown.…”
Section: Cd1dmentioning
confidence: 99%